RANCANG BANGUN PROTOTYPE KONVERSI SAMPAH PLASTIK POLYPROPYLENE MENJADI BAHAN BAKAR CAIR PROTOTYPE DESIGN OF CONVERSION POLYPROPYLENE PLASTIC WASTE INTO LIQUID FUEL - Tahdid, Tahdid (KINETIKA, 2019)
In Indonesia, there is very little waste treatment. Especially plastic waste that is difficult to decompose and difficult to process. Lack of handling of plastic waste and the number of people who use plastic cause the waste is endless. In this study, a prototype design was made to convert plastic waste into liquid fuel. Plastic waste is processed by the pyrolysis process. Plastic waste used is a type of Polypropylene (PP). In the pyrolysis process, plastic waste will be heated in the reactor so that it will produce gas and liquid in the form of oil and wax residues. The product is produced in the pyrolysis process with the raw material of Polyprolylen, which is a liquid fuel whose quality is close to gasoline